Health problems in vulvar condyloma bearers - Diógenes, Maria Albertina Rocha; Carvalho, Antônia Rita de Fátima Abreu de; Silva, Haleinia Hérica Rabelo (Rev Rene, 2009)
Vulvar condyloma is characterized by genital warts caused by the human papilloma virus, a sexually transmitted disease. With this research we aimed to identify self-care behaviors from requisites for health deviation in women with vulvar condyloma. It is a transversal study in an attendance sample of one of the researchers from a public institution which is reference in Sexually Transmitted Diseases in Fortaleza – CE, with 30 women between August and September 2007. An interview with open and closed questions was assigned and the data were analyzed descriptively. We observed that the interviewed women have low socioeconomic and educational level. The self-care behaviors identified in this research from the requisites for health problem were lack of knowledge about the disease, emotional inconstancy, partners’ lack of collaboration and financial difficulty to attend set appointments. Thus, knowing self-care behaviors for health problems in women with vulvar condyloma allowed us to notice that they present self-care deficit which are independent of their own will.